Parkinson’s disease motor intervention patterns: a network meta-analysis based on patient motor function - Zhao, Hongfei; Zhang, Li; Yang, Jingling; Guo, Wanru; Sun, Chunyang; Shi, Runbo; Wang, Zhen (Frontiers in Neurology, 2024)
Background: Parkinson's disease is characterized by symptoms such as bradykinesia and rigidity, which worsen as the disease progresses, significantly impacting patients' independence and quality of life. This study utilizes a network meta-analysis approach to quantify information gathered from randomized controlled trials (RCTs) regarding motor interventions that effectively improve the motor function of Parkinson's disease patients, aiming to provide evidence for selecting appropriate exercise intervention strategies for patients. Methods: A systematic search strategy for randomized controlled trials (RCTs) restricted to English was constructed based on multiple biomedical databases. Databases searched included PubMed, Embase, Cochrane, Web of Science, CINAHL, CBM, China National Knowledge Infrastructure (CNKI), Wan fang, VIP, etc., with searches conducted from inception to July 9, 2023. Two authors screened all studies, extracted data, and used frequency domain analysis methods. Network meta-analysis was performed using STATA software version 18.0 to compare and rank exercises that could effectively improve the motor function of Parkinson's disease patients (measured by indicators such as MDS-UPDRS-Ⅲ, TUG, BBS, Mini-BES Test, 6MWT scores). Additionally, a series of analyses and evaluations were conducted, such as assessing the methodological quality of included studies using the Cochrane risk of bias tool. Results: The network meta-analysis included a total of 111 studies involving 5,358 participants, 133 intervention experiments, and 31 intervention measures. Although most exercise interventions showed effectiveness, cumulative ranking curves under the surface (SUCRA) values showed that archery exercise significantly improved patients' MDS-UPDRS-Ⅲ scores (SUCRA=95.6%), significantly superior to routine care (standardized mean difference (SMD=16.92, 95%CI=-28.97, -4.87). Highintensity and agility exercise (High strength and agility) referred to as high-intensity exercise or agility training or a combination of both, collectively termed as high-intensity agility training, significantly improved patients' completion time for the time-up-and-go test (SUCRA=99.7%), . Dance and Tai Chi exercises significantly improved patients' balance abilities: Mini-Balance Evaluation Systems Test (SUCRA=77.9%), (SMD=5.25, 95%CI=-0.42,10.92). for dance intervention and Berg Balance Scale (SUCRA=94.7%), (SMD=11.22, 95%CI =3.26, 19.18). for Tai Chi intervention. Dance also significantly improved patients' walking ability in the 6-minute walk test (SUCRA=80.5%), (SMD=71.31, 95%CI=13.77, 128.84). Conclusion: Compared to other exercises, archery, dance, Tai Chi, and high-intensity agility exercises demonstrate superior efficacy in